Differences in the Time to Achieve Bromage Score (2) in Post-Spinal Anesthesia Caesarean Section Patients between the Use of Conventional Methods and Eracs - Norma Arlena; Dwi Novitasari; Asmat Burhan (Indonesian Journal of Global Health Research, 2025)
Pregnancy, labor, and delivery lead to significant physiological changes, and having accurate knowledge of these changes is crucial for an effective spinal anesthetic technique during a caesarean section. Optimizing the mother's health before, during, and after a caesarean section is the goal of the ERACS care method, which is a specialized approach to surgical procedures. Issues with lower limb mobility, anxiety, and dependence on others are some mental health problems that may arise from prolonged recovery periods. Spinal anesthesia patients are evaluated using the Bromage scale to determine if they are ready to be released from the post-anesthesia room. Researchers at Panglima Sebaya Hospital aimed to compare the time taken by standard operating room procedures and ERACS to reach a Bromage Score (2) after spinal anesthesia in caesarean section patients. This study employed a cross-sectional design based on observational analytical research, which is a non-experimental quantitative technique. Out of 84 patients, 47 were treated with standard SC techniques, and 47 were treated with ERACS SC. The findings indicated that the conventional method took 181–240 minutes (3–4 hours) to achieve a Bromage score (2), while the ERACS method only took 60–120 minutes (1–2 hours). A significance value of 0.000 (2-tailed) was determined based on the independent t-test results. The results showed that the ERACS method required less time than the conventional method to achieve Bromage Score (2) in CS patients post-spinal anesthesia.